The effectiveness of knowledge sharing: the case of ProMusa - Gotor, Elisabetta; Blundo Canto, Genowefa M.; Vezina, A. (2015)
In 2013, a study was undertaken to assess the nature and effectiveness of ProMusa from the point of view of its members and subscribers, what outputs are produced and how these are translated into outcomes and disseminated outside the network. The network provides the type and quality of services that its members expect: InfoMus@ and the mailing lists are the most successful service. An efficient and timely service on disease outbreaks and other breaking news is also a fundamental tool for ProMusa’s members and subscribers, and it should be a priority.